The phylogeny of mole crickets (Orthoptera: Gryllotalpoidea: Gryllotalpidae) - Cadena-Castañeda, Oscar J. (Zootaxa, 2015)
The monophyly and phylogenetic relationships of the family Gryllotalpidae were researched. Twenty-six in-group taxa, representing all known genera of Gryllotalpidae were included in a cladistic analysis, based on 89, morphological characters (including genital characters of the males). The different analyses of the resulting data matrix supported the monophyly of Scapteriscinae and Gryllotalpinae and its internal group. Subfamilies, tribes and genera of Gryllotalpidae are fully diagnosed, illustrated and keys to their identification are provided. Four tribes are established (Indioscaptorini n. trib. (Scapteriscinae), Triamescaptorini n. trib., Gryllotalpellini n. trib. and Neocurtillini n. trib. (Gryllotalpinae)) and two other are fully delimited (Scapteriscini stat. rev. and Gryllotalpini stat. rev.). Two new genera are described (Neoscapteriscus n. gen. and Leptocurtilla n. gen.) and as well as seven new species: Gryllotalpella rehni n. sp., G. tindalei n. sp., G. lawrencei n. sp., Neocurtilla ingrischi n. sp., N. townsendi n. sp., Leptocurtilla juanmanueli n. sp. and L. chopardi n. sp. The following nomenclatural changes were made: All species previously placed in Scapteriscus s.l. are transferred to the new genus Neoscapteriscus, except Scapteriscus oxydactilus and S. headsi that are still placed in Scapteriscus, Gryllotalpa chilensis reinst. stat. and Leptocurtilla maranona, n. comb. Finally, previous contributions about the phylogenetic relationships of molecrickets are contrasted with the results of this research.